A call to adapt the regulation of HLA testing for T cell receptor-based therapeutics: comment - Meyer, Miriam; Mahr, Andrea; Brewer, Joanna; Daniel, Volker; Dell‘Aringa, Justine; Goldstone, Tony; Hersey, Sarah; Johnston, Ian; Larson, Pamela; Loveridge, Michael; MacBeath, Gavin; Moyer, Mark; et al. (Nature reviews. Drug discovery, 2023)
Current regulation of T cell receptor (TCR)-based therapeutics may require repeated testing of patients for specific HLA alleles as well as companion diagnostics development, despite the invariant nature of the HLA genotype and availability of robust clinical HLA tests. This increases the burden on patients and the organizations developing these products. We propose regulatory flexibility to facilitate the development of and access to TCR-based therapeutics.
Gesehen am 05.11.2024